Blood donation history and eligibility assessment in a community‐based sample of men who have sex with men. Issue 4 (20th February 2018) - Custer, Brian; Murcia, Karla; Robinson, William T.; McFarland, Willi; Raymond, Henry Fisher
Abstract : BACKGROUND: In 2016, the US Food and Drug Administration changed the regulation from a permanent deferral from donation for men who have sex with men (MSM) to a 1‐year deferral since last sexual contact. It is unknown what proportions of MSM try to donate and if they would be willing to answer individual risk‐based questions to assess their current eligibility. STUDY DESIGN AND METHODS: The National HIV Behavioral Surveillance surveys periodically measure human immunodeficiency virus (HIV) prevalence and risk behaviors among MSM using a venue‐based, time‐location sampling method. In the 2014 cycle, that is, before the policy change, investigators in San Francisco and New Orleans added questions about blood donation. Questions inquired into three domains: donation history, policy awareness, and knowledge about HIV testing of donations. RESULTS: There were 404 and 557 respondents in San Francisco and New Orleans, respectively. Nearly one in three MSM in San Francisco (27.4%) and New Orleans (31.4%) tried to donate after their first MSM contact. A majority (63.1% in San Francisco, 58.8% in New Orleans) somewhat or strongly agreed that they would be willing to be asked detailed questions for donation eligibility assessment. CONCLUSIONS: The proportion of MSM who reported trying to donate was similar in the two cities. However, a substantial proportion did not agree to be asked more detailed risk behavior questions to assess eligibility. In these two geographic locations, prominent regional differences were not evident.